Efficacy of early prone or lateral positioning in patients with severe COVID-19: a single-center prospective cohort. Issue 4 (28th September 2020) - Ni, Zhong; Wang, Kaige; Wang, Ting; Ni, Yuenan; Huang, Wei; Zhu, Ping; Fan, Tao; Wang, Ye; Wang, Bo; Deng, Jun; Qian, Zhicheng; Liu, Jiasheng; et al.
Abstract: Background: Position intervention has been shown to improve oxygenation, but its role in non-invasively ventilated patients with severe COVID-19 has not been assessed. The objective of this study was to investigate the efficacy of early position intervention on non-invasively ventilated patients with severe COVID-19. Methods: This was a single-center, prospective observational study in consecutive patients with severe COVID-19 managed in a provisional ICU at Renmin Hospital of Wuhan University from 31 January to 15 February 2020. Patients with chest CT showing exudation or consolidation in bilateral peripheral and posterior parts of the lungs were included. Early position intervention (prone or lateral) was commenced for > 4 hours daily for 10 days in these patients, while others received standard care. Results: The baseline parameters were comparable between the position intervention group ( n  = 17) and the standard care group ( n  = 35). Position intervention was well-tolerated and increased cumulative adjusted mean difference of SpO2 /FiO2 (409, 95% CI 86 to 733) and ROX index (26, 95% CI 9 to 43) with decreased Borg scale (−9, 95% CI −15 to −3) during the first 7 days. It also facilitated absorption of lung lesions and reduced the proportion of patients with high National Early Warning Score 2 (≥ 7) on days 7 and 14, with a trend toward faster clinical improvement. Virus shedding and length of hospital stay were comparable between the two groups. Conclusions: This study provides the first evidence for improved oxygenation and lung lesion absorption using early position intervention in non-invasively ventilated patients with severe COVID-19, and warrants further randomized trials.